2009
DOI: 10.1007/s10456-009-9142-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PPARα-dependent and PPARα-independent transcript regulation following fenofibrate treatment of human endothelial cells

Abstract: Fenofibrate is a synthetic ligand for the nuclear receptor peroxisome proliferator-activated receptor (PPAR) alpha and has been widely used in the treatment of metabolic disorders, especially hyperlipemia, due to its lipid-lowering effect. The molecular mechanism of lipid-lowering is relatively well defined: an activated PPARalpha forms a PPAR-RXR heterodimer and this regulates the transcription of genes involved in energy metabolism by binding to PPAR response elements in their promoter regions, so-called "tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 33 publications
(55 reference statements)
1
33
0
Order By: Relevance
“…Expression of GDF15 and miR-3189-3p Is Increased after Fenofibrate Treatment-Previous reports have demonstrated that GDF15 expression is induced following treatment by a variety of chemotherapeutic agents (13,21,22). In line with these findings, we have also reported that this gene is up-regulated in a microarray analysis of glioblastoma cells treated with the metabolically active anticancer compound fenofibrate (4).…”
Section: Role Of Sf3b2 and P63rhogef In The Inhibition Of Cellular Prsupporting
confidence: 85%
See 1 more Smart Citation
“…Expression of GDF15 and miR-3189-3p Is Increased after Fenofibrate Treatment-Previous reports have demonstrated that GDF15 expression is induced following treatment by a variety of chemotherapeutic agents (13,21,22). In line with these findings, we have also reported that this gene is up-regulated in a microarray analysis of glioblastoma cells treated with the metabolically active anticancer compound fenofibrate (4).…”
Section: Role Of Sf3b2 and P63rhogef In The Inhibition Of Cellular Prsupporting
confidence: 85%
“…Similarly, anti-miR-3189-3p did not protect fenofibrate-treated cells from apoptosis, indicating that up-regulation of miR-3189-3p is not required for fenofibrate-mediated cell death. Given the broad range of anticancer effects triggered by fenofibrate (5,6,22,23,32,33) and the activity of a single microRNA, it is not surprising that miR-3189-3p is not contributing to the massive cell death mediated by fenofibrate. The microRNA itself seems to have a cytostatic rather than cytotoxic effect on the cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicate that FF may act in a PPAR␣-independent manner (5,12,14,18,20,30,37). To analyze these off-target effects, we subjected LN-229 human glioblastoma cells and NHA to subcellular fractionation following treatment with 50 M FF.…”
Section: Resultsmentioning
confidence: 99%
“…However, in comparison with the anticancer effects of other potent agonists of PPAR␣, those of FF are much more pronounced, implying that FF may also act in a PPAR␣-independent manner. In this regard, FF was shown to alter the expression of growth differentiation factor 15 (20); affect cell membrane fluidity in a manner similar to that of cholesterol (30); and interfere with the respiratory function of isolated liver and heart mitochondria (31,32). Here we report the novel observation that FF, but not its PPAR␣-active metabolite FA, accumulates in the mitochondrial fraction of human glioblastoma cells.…”
mentioning
confidence: 80%
See 1 more Smart Citation